Enhanced maximal exercise capacity, vasodilation to electrical muscle contraction, and hind limb vascular density in ASIC1a null mice. Issue 15 (7th August 2017) - Drummond, Heather A.; Xiang, Lusha; Chade, Alejandro R.; Hester, Robert
Abstract: Acid‐sensing ion channel (ASIC) proteins form extracellular proton‐gated, cation‐selective channels in neurons and vascular smooth muscle cells and are proposed to act as extracellular proton sensors. However, their importance to vascular responses under conditions associated with extracellular acidosis, such as strenuous exercise, is unclear. Therefore, the purpose of this study was to determine if one ASIC protein, ASIC1a, contributes to extracellular proton‐gated vascular responses and exercise tolerance. To determine if ASIC1a contributes to exercise tolerance, we determined peak oxygen (O2 ) uptake in conscious ASIC1a −/− mice during exhaustive treadmill running. Loss of ASIC1a was associated with a greater peak running speed (60 ± 2 vs. 53 ± 3 m·min −1, P  = 0.049) and peak oxygen (O2 ) uptake during exhaustive treadmill running (9563 ± 120 vs. 8836 ± 276 mL·kg −1 ·h −1, n  = 6–7, P  = 0.0082). There were no differences in absolute or relative lean body mass, as determined by EchoMRI. To determine if ASIC1a contributes to vascular responses during muscle contraction, we measured femoral vascular conductance (FVC) during a stepwise electrical stimulation (0.5–5.0 Hz at 3 V for 60 sec) of the left major hind limb muscles. FVC increased to a greater extent in ASIC1a −/− versus ASIC1a +/+ mice (0.44 ± 0.03 vs. 0.30 ± 0.04 mL·min −1 ·100 g hind limb mass −1 · mmHg −1, n  = 5 each, P  = 0.0009). Vasodilation following local application of external protons in the spinotrapezius muscle increased the duration, but not the magnitude, of the vasodilatory response in ASIC1a −/− mice. Finally, we examined hind limb vascular density using micro‐CT and found increased density of 0–80  μ m vessels ( P  <   0.05). Our findings suggest an increased vascular density and an enhanced vasodilatory response to local protons, to a lesser degree, may contribute to the enhanced vascular conductance and increased peak exercise capacity in ASIC1a −/− mice. Abstract : Metabolic factors, such as extracellular acidosis, contribute to local vasodilation and hyperemia during skeletal muscle contraction. Here, we show that ASIC1a, a protein that forms ion channels gated by extracellular protons, negatively contributes to local control of skeletal muscle vascular diameter, blood flow, and exercise capacity.